A Well-Known Lesion in An Unusual Location: Infantile Myofibroma of the Eyelid:A Case Report and Review of Literature - Fahimeh Asadi Amoli; Amir Hossein Sina; Aboulfazl Kasai; Zahra Ayan (Acta Medica Iranica, 2010)
"nMyofibroma is a neoplasia of myofibroblasts that can be solitary or multiple and it is found most commonly in the head & neck region including scalp, forehead, parotid region and oral cavity. In the eyelid it is rarely reported. It has a benign course in the solitary form and fatal in its multiple form. A 4 month male infant referred to Farabi hospital -the referral center for eye diseases- with a 2 month history of a mass in his eyelid with gradual enlargement with no other complaints. The only abnormal physical finding was a 2.5 cm mass in the eyelid. This mass was excised and sent to the hospital pathology laboratory. When confronting a spindle cell lesion with a nodular or multinodular growth pattern which appears biphasic due to alteration of light and dark staining areas, the surgical pathologist should think to the possibility of myofibroma. Its pattern of growth and architecture rules out the other differential diagnoses like nodular fasciitis, fibrous histiocytoma, infantile fibromatosis, and peripheral primitive neuroectodermal tumor, mesenchymal chondrosarcoma, malignant hemangiopericytoma, juvenile fibrosarcoma and poorly differentiated synovial sarcoma. In difficult cases immunohistochemical staining is helpful that is Vimentin & Actin positivity & Desmin, CK, EMA & S100 negativity.